Aspectele practice referitoare la soluţionarea litigiilor de muncă de către instanţa de judecată - Macovei, Tatiana; Macovei, Gheorghe (CEP USM, 2024)
Labor disputes that have not been settled amicably by the employer and the employee can be settled by the court if the employee applies for a summons. in this communication we propose to address the most important aspects that refer to the resolution of individual labor disputes by the court. In the vast majority of cases, employees have the status of plaintiff when examining individual labor disputes, employers have the status of employee only in one category of litigation - bringing employees to material liability.
PRACTICAL ASPECTS REGARDING THE SOLUTION OF INDIVIDUAL LABOR LITIGATIONS BY COURT
Keywords: employee; employer; litigation; evidence; court; salariat; angajator; litigiu; probe; instanța de judecată